Effect of chemical cleaning on nanofiltration process in treating surface water. (December 2022) - Zhang, Xinyang; Gan, Zhendong; Wang, Yanrui; Tang, Xiaobin; Li, Guibai; Liang, Heng
Abstract: Nanofiltration (NF) has been increasingly used in drinking water treatment plants; however, the severe membrane fouling caused by organic matter poses great challenges to the application of NF technology. This study investigated the mitigation of NF membrane fouling by different chemical cleaning reagents (e.g., citric acid, NaOH, Na4 -EDTA, and Na-SDS), Na4 -EDTA and Na-SDS performed better to achieve NF permeability recovery of up to 90.5–94.2 % just in a single chemical cleaning cycle. The hydraulic irreversible membrane fouling could be reduced by 44.9–53.8 % in the multi-cycle operation of chemical cleaning. Na4 -EDTA-based cleaning was beneficial to the removal performance of sulfamethazine (SM2) and conferred higher removal efficiency than Na-SDS-based cleaning efficiency. The impact of chemical cleaning on energy consumption was evaluated and indicated that Na4 -EDTA-based cleaning could reduce the proportion of unfavorable energy consumption by 4.54 %. The operation stability of the NF process could be effectively improved by chemical cleaning, and the organic pollutants accumulated on the membrane surface can be removed, especially the chemical cleaning using Na4 -EDTA and Na-SDS. These findings could improve the operational efficiency of the NF process with low energy consumption, low chemical consumption, and less adverse environmental impact. Graphical abstract: Unlabelled Image Highlights: Na-SDS-based cleaning recovered the NF permeability up to 94.2 %. Na4 -EDTA-based cleaning had a better effect in irreversible fouling control. Na4 -EDTA/Na-SDS alleviated membrane fouling by coordination/bridging effects. Energy consumption reduction of chemical cleaning in NF process was quantified.